PLANT PREBIOTICS AND HUMAN HEALTH: BIOTECHNOLOGY TO BREED PREBIOTIC-RICH NUTRITIOUS FOOD CROPS - PROF. PICHOULE SHINDE, PROF.DROBPRY (International Journal of Multidisciplinary Research and Studies, 2021)
Microbiota within the gut plays essential roles in human health. Prebiotics are non-digestible complex carbohydrates that are fermented within the colon, yielding energy and short-chain fatty acids, and selectively promote the expansion of Bifidobacteria and Lactobacillus within the digestive tract. Fructans and inulin are the best-characterized plant prebiotics. Many vegetable, root, and tuber crops similarly as some fruit crops are the best-known sources of prebiotic carbohydrates, while the prebiotic-rich grain crops include barley, chickpea, lentil, lupin, and wheat. Some prebiotic-rich crop germplasm has been reported in barley, chickpea, lentil, wheat, yacon, and Jerusalem artichoke. some major quantitative trait loci and gene-based markers related to high fructan are known in wheat. More targeted search in genebanks using reduced subsets (representing diversity in germplasm) is required to spot accessions with prebiotic carbohydrates. Transgenic maize, potato, and sugarcane with high fructan, with no adverse effects on plant development, are bred, which suggests that it’s feasible to introduce fructan biosynthesis pathways in crops to supply health-imparting prebiotics. Developing prebiotic-rich and super nutritious crops will alleviate widespread malnutrition and promote human health. A paradigm shift in a very breeding program is required to realize this goal and to confirm that newly-bred crop cultivars are nutritious, safe, and health-promoting